2021
DOI: 10.2298/jsc200705049s
|View full text |Cite
|
Sign up to set email alerts
|

Crystal products of lamotrigine-citric acid for improvement of in vitro drug release in simulated gastric fluid

Abstract: Crystal engineering is an integral part of the drug development research. Crystal forms can modify the physicochemical properties of the parent drug molecule. The present work was aimed at the synthesis and characterization of crystalline product of lamotrigine (LT), a FDA approved anti-epileptic drug, with citric acid (CA) to improve its release in gastric region and oral absorption. The crystalline products of LT-CA were developed by solvent evaporation method using ethanol-water as the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In vitro dissolution of aspirin of the films was carried out in the USP type II dissolution apparatus (Electolab, TDT06L, India) by utilizing 200 ml phosphate buffer (pH 6.8) as dissolution media at 34.0 ± 0.2 °C and 50 rpm for 6 h. 18,[31][32][33] A piece of film, weighing between 55-72 mg was cut and attached to the glass slide using cyanoacrylate glue and carefully placed it into the bottom of the vessel containing the dissolution medium. At different time intervals, 10 ml of the samples were withdrawn through a membrane filter (0.45 µm, syringe driven) and the same volume was replaced in each vessel with fresh medium.…”
Section: In Vitro Dissolution Of Drugmentioning
confidence: 99%
“…In vitro dissolution of aspirin of the films was carried out in the USP type II dissolution apparatus (Electolab, TDT06L, India) by utilizing 200 ml phosphate buffer (pH 6.8) as dissolution media at 34.0 ± 0.2 °C and 50 rpm for 6 h. 18,[31][32][33] A piece of film, weighing between 55-72 mg was cut and attached to the glass slide using cyanoacrylate glue and carefully placed it into the bottom of the vessel containing the dissolution medium. At different time intervals, 10 ml of the samples were withdrawn through a membrane filter (0.45 µm, syringe driven) and the same volume was replaced in each vessel with fresh medium.…”
Section: In Vitro Dissolution Of Drugmentioning
confidence: 99%
“…DSC characterization produces a thermogram that can provide information about the thermal properties and solids phase transformation of the sample due to interactions between components in the sample (Satapathy et al, 2021;Thorat et al, 2021;Wicaksono et al, 2020). DSC thermograms of solids of atorvastatin calcium, dipicolinic acid, and atorvastatin calcium-dipicolinic acid are shown in Figure 3.…”
Section: Dsc Thermogrammentioning
confidence: 99%
“…The molecules of atorvastatin calcium and dipicolinic acid in the multicomponent solids form intermolecular interactions that produce a new solids phase. The multicomponent solids atorvastatin calcium-dipicolinic acid has a different molecular arrangement than the individual solids of its constituent materials (Satapathy et al, 2021). Different molecular arrangements cause changes in the pattern of molecular arrangement in the solids system and produce new crystal packing with different crystal lattice energies (Volodin et al, 2020;Kilinkissa et al, 2020;Ejarque et al, 2021).…”
Section: Dsc Thermogrammentioning
confidence: 99%
See 1 more Smart Citation
“…Similar reports for the use of water as release medium for poorly soluble drugs have already been reported earlier including ibuprofen. 17,[23][24][25][26][27][28][29][30][31][32][33] Hu et al reported in vitro drug release of IBU from the experimental micro emulsion in distilled water. 26 It was found that in vitro release profiles of IBU did not show much change in different drug release medium, i.e.…”
Section: Dissolution Of Drugmentioning
confidence: 99%